Surface albedo and thermal radiation dynamics under conservation and conventional agriculture in subhumid Zimbabwe - Diop, Souleymane; Cardinael, Rémi; Lauerwald, Ronny; Ferlicoq, Morgan; Thierfelder, Christian; Chikowo, Regis; Corbeels, Marc; Affholder, François; Baudron, Frédéric; Ceschia, Eric (Elsevier, 2026)
While conservation agriculture (CA) has been widely evaluated for its biogeochemical effects (e.g soil organic carbon sequestration and greenhouse gas emissions) for climate mitigation, its biogeophysical impacts related to changes in surface albedo remain understudied. This study assessed the biogeophysical effects of CA cropping systems with maize (Zea mays L.) in Zimbabwe. Measurements were conducted continuously over two cropping years at two long-term experiments with contrasting soil characteristics, on an abruptic Lixisol and on a xanthic Ferralsol. The dynamics of surface albedo, longwave radiation, leaf area index, soil moisture and temperature were monitored under three different treatments: conventional tillage (CT, tilled to ∼15 cm), no-tillage (NT) and no-tillage with mulch (NTM, 2.5 t DM ha⁻¹). Our results revealed that, on the Ferralsol, NT and NTM significantly (p < 0.05) increased mean annual albedo (0.17) relative to CT (0.16), resulting in a negative instantaneous radiative forcing (iRF) and indicating a net cooling effect. iRF was stronger in 2021/22 (NT: -0.83 ± 0.17 W m-2; NTM: -1.43 ± 0.7 W m-2) than in 2022/23 (NT: -0.43 ± 0.09 W m-2; NTM: -1.03 ± 0.21 W m-2). Conversely, on the Lixisol, while NT increased surface albedo (0.27 vs. CT: 0.24), NTM significantly reduced albedo (0.23), causing positive iRF (warming). iRF was -3.34 ± 0.69 W m-2 and -2.78 ± 0.77 W m-2 for NT in the first and second cropping year, respectively, and increased from 1.14 ± 0.21 W -2 (2021/22) to 2.77 ± 0.41 W m-2 (2022/23) under NTM. Overall, our results suggest that the soil background albedo is an important site characteristic that needs to be considered and demonstrates the importance of considering biogeophysical effects when promoting practices of CA for climate change mitigation.